What Every Woman Should Know About Painting - National Paint, Varnish (Pamphlets corresponding to radio shows produced by the National Paint, Varnish and Lacquer Association, 1940)
Booklet corresponding to a radio broadcast program created by the National Paint, Varnish, and Lacquer Association. The booklet describes how there is much to consider prior to beginning a painting project. It likens potential painting obstacles such as moisture, heat, or wind to villains in "old-time plays." Asserts that the painter must outwit them by having prepared for the project in advance. Discusses color scheming and a variety of tips and tricks for painting a house. Includes small stylized illustrations throughout and decorated covers. The National Paint, Oil and Varnish Association, Inc., formed in 1933, was the national professional association representing all branches of the paint, oil, and varnish industries.
Keywords: Shellac; Paint materials; Linseed oil; Oilseeds; Varnish and varnishing; Varnish industry; Paint industry and trade; Advertising--Paint; Sexism; Stereotypes (Social psychology) in advertising